International standards of journalism: theory of freedom of expression and access to information (Herald of Journalism, 2020)
Creation of a legal civil society has been one of the recognized pre- requisites for promotion of any modern state on the path of major social and economic reforms, one of the objectives of its modernization. This idea came to legislation and public consciousness of most modern coun- tries and nations. The highest measure of the degree of civilization of a society was the human rights situation in a particular country. Freedom of opinion and expression, freedom of the media constitute the foundations of modern society and a democratic state. Following philosophical theo- ries, probably to consider a freedom of speech as a special case of a free- dom of expression. At the level of the international instruments numerous key characteristics of such a media environment are identified in which   to flourish freedom of expression, independence and pluralism, based on the principles outlined in Windhoek Declaration (1991) and subsequent declarations of regional seminars to promote independent and pluralistic media (Almaty, Santiago, Sana’a and Sofia).
Keywords: media, legal regulation, access to information, information security.